Упростите вырожение [tex](\frac{1}{x-1}-\frac{x+1}{x^{2}+x+1}):(1+\frac{1}{x^{3}-1}[/tex])
решние во вложении
------------------
1)
2)
3)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
решние во вложении
------------------
Verified answer
1)![\frac{1}{x-1}-\frac{x+1}{x^{2}+x+1}=\frac{x^{2}+x+1-(x+1)(x-1)}{(x-1)(x^{2}+x+1)}= \frac{x^{2}+x+1-(x^{2}-x+x-1)}{(x-1)(x^{2}+x+1)}=\frac{x^{2}+x+1-(x^{2}+(-x+x)-1)}{(x-1)(x^{2}+x+1)}= \frac{1}{x-1}-\frac{x+1}{x^{2}+x+1}=\frac{x^{2}+x+1-(x+1)(x-1)}{(x-1)(x^{2}+x+1)}= \frac{x^{2}+x+1-(x^{2}-x+x-1)}{(x-1)(x^{2}+x+1)}=\frac{x^{2}+x+1-(x^{2}+(-x+x)-1)}{(x-1)(x^{2}+x+1)}=](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx-1%7D-%5Cfrac%7Bx%2B1%7D%7Bx%5E%7B2%7D%2Bx%2B1%7D%3D%5Cfrac%7Bx%5E%7B2%7D%2Bx%2B1-%28x%2B1%29%28x-1%29%7D%7B%28x-1%29%28x%5E%7B2%7D%2Bx%2B1%29%7D%3D%20%5Cfrac%7Bx%5E%7B2%7D%2Bx%2B1-%28x%5E%7B2%7D-x%2Bx-1%29%7D%7B%28x-1%29%28x%5E%7B2%7D%2Bx%2B1%29%7D%3D%5Cfrac%7Bx%5E%7B2%7D%2Bx%2B1-%28x%5E%7B2%7D%2B%28-x%2Bx%29-1%29%7D%7B%28x-1%29%28x%5E%7B2%7D%2Bx%2B1%29%7D%3D)
![\frac{x^{2}+x+1-(x^{2}-1)}{x^{3}-1}=\frac{x^{2}+x+1-x^{2}+1}{x^{3}-1}=\frac{(x^{2}-x^{2})+x+(1+1)}{x^{3}-1}=\frac{x+2}{x^{3}-1} \frac{x^{2}+x+1-(x^{2}-1)}{x^{3}-1}=\frac{x^{2}+x+1-x^{2}+1}{x^{3}-1}=\frac{(x^{2}-x^{2})+x+(1+1)}{x^{3}-1}=\frac{x+2}{x^{3}-1}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D%2Bx%2B1-%28x%5E%7B2%7D-1%29%7D%7Bx%5E%7B3%7D-1%7D%3D%5Cfrac%7Bx%5E%7B2%7D%2Bx%2B1-x%5E%7B2%7D%2B1%7D%7Bx%5E%7B3%7D-1%7D%3D%5Cfrac%7B%28x%5E%7B2%7D-x%5E%7B2%7D%29%2Bx%2B%281%2B1%29%7D%7Bx%5E%7B3%7D-1%7D%3D%5Cfrac%7Bx%2B2%7D%7Bx%5E%7B3%7D-1%7D)
2)![1+\frac{1}{x^{3}-1}=\frac{x^{3}-1+1}{x^{3}-1}=\frac{x^{3}+(-1+1)}{x^{3}-1}=\frac{x^{3}}{x^{3}-1} 1+\frac{1}{x^{3}-1}=\frac{x^{3}-1+1}{x^{3}-1}=\frac{x^{3}+(-1+1)}{x^{3}-1}=\frac{x^{3}}{x^{3}-1}](https://tex.z-dn.net/?f=1%2B%5Cfrac%7B1%7D%7Bx%5E%7B3%7D-1%7D%3D%5Cfrac%7Bx%5E%7B3%7D-1%2B1%7D%7Bx%5E%7B3%7D-1%7D%3D%5Cfrac%7Bx%5E%7B3%7D%2B%28-1%2B1%29%7D%7Bx%5E%7B3%7D-1%7D%3D%5Cfrac%7Bx%5E%7B3%7D%7D%7Bx%5E%7B3%7D-1%7D)
3)![\frac{x+2}{x^{3}-1}:\frac{x^{3}}{x^{3}-1}=\frac{x+2}{x^{3}-1}\cdot\frac{x^{3}-1}{x^{3}}=\frac{x+2}{x^{3}} \frac{x+2}{x^{3}-1}:\frac{x^{3}}{x^{3}-1}=\frac{x+2}{x^{3}-1}\cdot\frac{x^{3}-1}{x^{3}}=\frac{x+2}{x^{3}}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%2B2%7D%7Bx%5E%7B3%7D-1%7D%3A%5Cfrac%7Bx%5E%7B3%7D%7D%7Bx%5E%7B3%7D-1%7D%3D%5Cfrac%7Bx%2B2%7D%7Bx%5E%7B3%7D-1%7D%5Ccdot%5Cfrac%7Bx%5E%7B3%7D-1%7D%7Bx%5E%7B3%7D%7D%3D%5Cfrac%7Bx%2B2%7D%7Bx%5E%7B3%7D%7D%20)